Design Development and Ex vivo Evaluation of Dorzolamide Nanoparticles Laden Contact Lens for Management of Glaucoma - Koirala, Sagar; Sudheer, Preethi; Thomas, Litha; Alur, Ashwini; Srinivasan, Johnsi (Indian Journal of Pharmaceutical Education and Research, 2025)
Background: The current study aimed to design dorzolamide hydrochloride nanoparticle (NP)-laden contact lenses to control drug release for the effective management of glaucoma. Materials and Methods: Ionotropic gelation technique, using chitosan and sodium tripolyphosphate as the polymer and cross-linking agent, respectively, was employed for the formulation of nanoparticles. The formulation trials were optimized using a factorial design with JMP Pro software. The ANOVA-supported optimum formula (S6) was evaluated for particle size, zeta potential, FTIR, drug entrapment efficiency, morphology, in vitro drug release profile, and ex vivo permeation. Optimized nanoparticles were loaded into the contact lens using the soaking method, and the loaded contact lens was characterized for appearance, optical clarity, swelling equilibrium, in vitro release, ex vivo transcorneal permeation, and short-term stability. Results: The optimized formulation S6 exhibited a mean particle size of 55.7 nm and zeta potential of 25.6 mV. Scanning electron microscopy revealed that the nanoparticles were irregularly shaped with uneven and dense surfaces. Furthermore, ex vivo permeation studies of the optimized nanoparticles exhibited a higher flux and permeability coefficient than the pure drug solution and marketed eye drops. The nanoparticle-laden contact lenses were visually transparent and had a transmittance of 94.10±30.21%, similar to that of the control lenses. In addition, it showed less swelling and exhibited drug release 71.79±0.17% in 12 h. The ex vivo permeation studies exhibited good permeation, and drug loss during the storage period was insignificant
Keywords: xxx